2019
DOI: 10.1155/2019/7593608
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Alleviates Amyloid β-Induced Mitochondrial Dysfunction and Synaptic Loss

Abstract: Synaptic structural and functional damage is a typical pathological feature of Alzheimer’s disease (AD). Normal axonal mitochondrial function and transportation are vital to synaptic function and plasticity because they are necessary for maintaining cellular energy supply and regulating calcium and redox signalling as well as synaptic transmission and vesicle release. Amyloid-β (Aβ) accumulation is another pathological hallmark of AD that mediates synaptic loss and dysfunction by targeting mitochondria. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 44 publications
(46 reference statements)
0
32
0
Order By: Relevance
“…In our next study, we plan to examine differences in gut microbiota in berberineand non-berberine treated mice as we hypothesize that these differences might be associated with differences in relapse propensity. Furthermore, a number of studies found that berberine has multifunctional properties and can inhibit the activity of important pathogenic enzymes, ameliorate intracellular oxidative stress, attenuate neuroinflammation, trigger autophagy, and protect neurons against recognition memory damage (de Oliveira et al, 2019;Yuan et al, 2019;Zhao et al, 2019). Undeniably, more research is needed to understand the effects of pre-extinction berberine intervention on relapse and uncover the underlying neurochemical and molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In our next study, we plan to examine differences in gut microbiota in berberineand non-berberine treated mice as we hypothesize that these differences might be associated with differences in relapse propensity. Furthermore, a number of studies found that berberine has multifunctional properties and can inhibit the activity of important pathogenic enzymes, ameliorate intracellular oxidative stress, attenuate neuroinflammation, trigger autophagy, and protect neurons against recognition memory damage (de Oliveira et al, 2019;Yuan et al, 2019;Zhao et al, 2019). Undeniably, more research is needed to understand the effects of pre-extinction berberine intervention on relapse and uncover the underlying neurochemical and molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The study findings confirmed that berberine may preserve mitochondrial membrane potential, improve mitochondrial motility and prevent synaptic loss. 105 Caffeine is a naturally occurring CNS stimulant found in coffee, tea, and other plants. It has been used for medicinal purposes in many systems of traditional medicine for over thousands of years.…”
Section: Phytochemicalsmentioning
confidence: 99%
“…BBR exerts anti-platelet aggregation, stable plaque, and antiatherosclerotic effects Zhao et al, 2019).…”
Section: Berberine (Bbr)mentioning
confidence: 99%